2021
DOI: 10.2147/ccid.s322228
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Active Ingredients in Cosmetic Products for the Care of Skin That Has Been Exposed to Ionizing Radiation – Analysis of Their Effectiveness in Breast Cancer Radiotherapy

Abstract: Treatment that uses ionizing radiation is one of the most common therapeutic methods in case of breast cancer. However, it often results in radiation dermatitis, which manifests itself, among others, as erythema, burning, itching and pain as well as dry or moist desquamation of the epidermis in the irradiated areas. The intensity of these symptoms significantly reduces the patient’s quality of life, which could affect the effectiveness of the entire therapy. There are more and more cosmetic preparations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
2
0
3
Order By: Relevance
“…This is particularly beneficial for atopic dogs, whose compromised skin barrier and predisposition to dehydration demand careful consideration of moisturisation strategies. Studies have demonstrated the hydrating properties of both glycerine and allantoin, emphasising their importance in formulations targeting skin health and integrity [ 23 , 24 ]. Therefore, the inclusion of these ingredients in chlorhexidine wipes presents a synergistic approach to managing dysbiosis while supporting skin hydration, crucial in the management of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly beneficial for atopic dogs, whose compromised skin barrier and predisposition to dehydration demand careful consideration of moisturisation strategies. Studies have demonstrated the hydrating properties of both glycerine and allantoin, emphasising their importance in formulations targeting skin health and integrity [ 23 , 24 ]. Therefore, the inclusion of these ingredients in chlorhexidine wipes presents a synergistic approach to managing dysbiosis while supporting skin hydration, crucial in the management of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados favorables conseguidos con los productos del kit, así como con otros dermocosméticos prescritos en pacientes en tratamiento oncológico para prevenir los efectos tóxicos en piel, se deben a las propiedades de sus componentes. Estos contribuyen al fortalecimiento y regeneración de la estructura de la piel, conservan la hidratación de la barrera epidérmica, mantienen la piel limpia y libre de impurezas, aportan efectos antimicrobianos, son gentiles al contacto con la piel y los anexos, tienen potencial capacidad para la eliminación de radicales libres, son antioxidantes, antiinflamatorios y cicatrizantes 15,[18][19][20] .…”
Section: Discussionunclassified
“…Sumando a lo anterior, a partir de los resultados favorables en cuanto a la aceptación, tolerancia, evolución clínica y de la calidad de vida con los productos del kit, así como con otros dermocosméticos, se considera la posibilidad de un efecto sinérgico entre los productos de origen farmacológico y dermocosmético, los cuales en conjunto podrían impactar positivamente sobre los desenlaces clínicos. Aunque también, teniendo en cuenta la receptividad por parte de los pacientes y el buen desempeño de los dermocosméticos, el inicio de fármacos podría ser diferido para casos con un nivel de compromiso en piel moderado o severo, que no mejore con las medidas no farmacológicas 19,20,24,25 .…”
Section: Discussionunclassified
“…Um diesen präventiv zu begegnen, wurden Strategien zur protektiven Anwendung von speziellen Pflegetherapeutika entwickelt und klinisch validiert [ 39 ]. Auch für die kutanen Reaktionen nach Radiatio bei Mammakarzinom liegen Evidenzen zu pflegetherapeutischen Strategien vor [ 40 ].…”
Section: Besonderheiten Der Topischen Therapieunclassified